THE ROLE AND IMPORTANCE OF TOURISM INFRASTRUCTURE IN THE DEVELOPMENT OF REGIONAL TOURISM (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article focuses on the challenges of developing regional tourism infrastructure. The article also defines the essence of the concept of